Rizzoli & Isles. The seventh and final season [videorecording (DVD)] - Gerritsen, Tess; Harmon, Angie, 1972-; Alexander, Sasha, 1973-; Bridges, Jordan, 1973-; McGill, Bruce, 1950-; Bracco, Lorraine, 1955-; Tamaro, Janet (Warner Bros. Home Entertainment, 2017)
The seventh and final season of the show, which is as thrilling and dangerous as the show has ever been, opens in the aftermath of a shooting that took place in the prior season's finale episode. The team must use every tool at their disposal to find the elusive Alice Sands they've been hunting for, and bring her to justice before she succeeds in destroying Jane's life.